The Impact of MGMT Promoter Methylation and Temozolomide Treatment in Serbian Patients with Primary Glioblastoma - Nikola Jovanović; Tatjana Mitrović; Vladimir J. Cvetković; Svetlana Tošić; Jelena Vitorović; Slaviša Stamenković; Vesna Nikolov; Aleksandar Kostić; Nataša Vidović; Miljan Krstić; Tatjana Jevtović-Stoimenov; Dušica Pavlović (Medicina, 2019)
Background and objective: Despite recent advances in treatment, glioblastoma (GBM) remains the most lethal and aggressive brain tumor. A continuous search for a reliable molecular marker establishes the methylation status of the O6-methylguanine-DNA methyltransferase (MGMT) gene promoter as a key prognostic factor in primary glioblastoma. The aim of our study was to screen Serbian patients with primary glioblastoma for an MGMT promoter hypermethylation and to evaluate its associations with overall survival (OS) and sensitivity to temozolomide (TMZ) treatment. Materials and methods: A cohort of 30 Serbian primary glioblastoma patients treated with radiation therapy and chemotherapy were analyzed for MGMT promoter methylation and correlated with clinical data. Results: MGMT methylation status was determined in 25 out of 30 primary glioblastomas by methylation-specific PCR (MSP). MGMT promoter hypermethylation was detected in 12 out of 25 patients (48%). The level of MGMT promoter methylation did not correlate with patients’ gender (p = 0.409), age (p = 0.536), and OS (p = 0.394). Treatment with TMZ significantly prolonged the median survival of a patient (from 5 to 15 months; p < 0.001). Conclusions: Due to a small cohort of primary GBM patients, our study is not sufficient for definitive conclusions regarding the prognostic value of MGMT methylation for the Serbian population. Our preliminary data suggest a lack of association between MGMT promoter methylation and overall survival and a significant correlation of TMZ treatment with overall survival. Further population-based studies are needed to assess the prognostic value of the MGMT promoter methylation status for patients with primary glioblastoma.